2019
DOI: 10.1519/ssc.0000000000000395
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Penultimate Foot Contact During Change of Direction: Implications on Performance and Risk of Injury

Abstract: Most change of direction biomechanical investigations and current technique guidelines focus on the role of the final foot contact (plant foot contact). However, it is evident that the braking characteristics during the penultimate foot contact play an integral role in deceleration prior to directional changes ≥ 60˚; and can therefore, be described as a "preparatory step". In this review, we examine the role of the penultimate foot contact on change of direction performance and associated biomechanical injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(118 citation statements)
references
References 85 publications
(120 reference statements)
1
114
1
2
Order By: Relevance
“…Faster performance was also found for the turns from the kicking limb which could partially be attributed to the female athletes displaying greater horizontal braking forces in the penultimate foot contact relative to the final foot contact; thus, a greater horizontal ground reaction force ratio in their D limb turn. This finding is noteworthy because high magnitudes of penultimate foot contact braking forces relative to the final foot contact have been identified as a determinant of faster 180° turning performance [53,54]. Furthermore, Nimphius et al [22] reported a 27.4% asymmetry in COD deficit for a female athlete, and attributed the differences based on qualitative assessments of the braking and turning strategies between directions.…”
Section: Discussionmentioning
confidence: 98%
“…Faster performance was also found for the turns from the kicking limb which could partially be attributed to the female athletes displaying greater horizontal braking forces in the penultimate foot contact relative to the final foot contact; thus, a greater horizontal ground reaction force ratio in their D limb turn. This finding is noteworthy because high magnitudes of penultimate foot contact braking forces relative to the final foot contact have been identified as a determinant of faster 180° turning performance [53,54]. Furthermore, Nimphius et al [22] reported a 27.4% asymmetry in COD deficit for a female athlete, and attributed the differences based on qualitative assessments of the braking and turning strategies between directions.…”
Section: Discussionmentioning
confidence: 98%
“…Although the frequencies of high-intensity accelerations have been shown to be different between positional roles in hockey, the relative frequency of high-intensity decelerations was similar across all positions (0.9–1.0 n·min). As the ability to decelerate at high intensity can also influence a player’s change of direction performance [82], these actions may have particular importance to hockey match-play performance outcomes. Furthermore, both high-intensity accelerations and decelerations have been shown to be the match-activity variables most sensitive to fatigue development during hockey match play [18].…”
Section: Discussionmentioning
confidence: 99%
“…The COD speed and training intervention focused on modifying biomechanical deficits associated with increased injury-risk [14,22,27] and promoting techniques required for faster performance [14,22,23,24]. For example, the programme focused on several aspects: a wide foot-plant is required for medio-lateral propulsive impulse generation and subsequent exit velocity during cutting [22,24]; faster performance and lower knee joint loading has been associated with increased PFC braking forces [41]; and trunk lean towards the direction of travel and reduced lateral trunk flexion is associated with faster performance and reduced knee joint loads [14,22,23]. Moreover, knee valgus is also a hazardous “high-risk” posture [56] with no associated performance benefits [14,23,24] and thus, was a further desired technical change in response to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The six-week technique modification intervention focused on pre-planned low-intensity decelerations and turns (weeks 1–2), before progressing intensity via velocity and angle (weeks 3–4) [27,36,39], and introducing a stimulus with increased intensity (weeks 3–6). The COD programme was in accordance with COD speed recommendations from the National Strength and Conditioning Association [40], Nimphius [5], and recent braking-strategy recommendations [41], and the duration, distances, and number of CODs were similar to previously successful 6-week COD speed [6,7,8] and COD technique modification studies [13,25]. The sessions were led by the principle investigator, who is a certified strength and conditioning specialist with extensive experience in coaching COD speed and agility drills.…”
Section: Methodsmentioning
confidence: 99%